Mbok: Its distribution, meaning, and function - Ajar Pradika A. Tur (Journal on English as a Foreign Language, 2015)
Mbok, in Javanese language, has not only a ’mother’ in meaning. As a lexicon in the language, mbok in one side truly means a ‘mother’ and still has the same meaning although it experiences the morphological process to be, at least, embok, simbok, or mboke. The variations exist and are spoken by Javanese native speakers throughout the Javanese dialects such as Suroboyoan, Solo, Yogyakarta, Bagelen, and Banyumasan dialects spread from the East Java, Yogyakarta, and Central Java. However, mbok, as a particle has different meaning, even different various meanings relying on its distribution in a sentence. Then the meanings bear its different various functions as well in the sentence based on the context of the sentence (grammatical-semantics meaning). Through Teknik Balik (Converse Technique) the data gained was analyzed to distinguish the position of the particle in the sentence in order to reach its significant different meanings and functions. At least, from the analysis, we have three positions of mbok in the sentences, that are in the initial, middle, and the end of the sentences. These positions affect the meanings and functions that can be seen as follows; ‘, is not it?’ (Tag Question) and ‘is/are” (Verbal Question) for emphasizing, ‘please’ for requesting a help, ‘may be’ and ‘in case’ for expressing possibility, and ‘causing’ for expressing cause-effect.